VICTIMOLOGY ANALYSIS OF SOCIETAL LABELING ON FEMALE UNIVERSITY STUDENTS WHO VISIT NIGHTCLUBS (A STUDY ON X, Y, AND Z IN PEKANBARU) - Vira Novella; M. Zulherawan (CV. Tirta Pustaka Press, 2025)
The phenomenon of female university students visiting nightclubs often triggers negative societal labeling that shapes their identity and social position. This study aims to explore the motivations behind such behavior, the forms of stigma received, and the psychological and social impacts experienced. Employing a qualitative approach with purposive sampling. data were collected through in-depth interviews with three student informants (X, Y, Z) and supported by additional community informants. The data were analyzed using a thematic analysis framework to identify recurring patterns of meaning. The findings reveal that motivations include curiosity, peer influence, entertainment needs, and coping mechanisms for academic or family-related stress. The students experience stigmatizing labels such as “party girl” or “immoral,” which contribute to feelings of shame, insecurity, and social withdrawal. Due to the limited number of key informants, the findings cannot be generalized but provide an in-depth understanding of the social victimization experienced by these students. The study highlights how societal stigma functions as a form of secondary victimization that impacts their well-being and social interactions.